Colossal magnetocaloric effect in Ni–Co–Mn–In alloys induced by electron irradiation. (December 2020) - Sun, S.; Qin, H.; Wang, H.; Ning, R.; Zhao, Y.; Zhu, J.; Gao, Z.; Cong, D.; Wang, Y.; Cai, W.
Abstract: Magnetocaloric materials have shown huge potential for magnetic refrigeration but fail meeting the application standard because of the low magnetic entropy change Δ S M . In this work, high-energy electron irradiation is used to enlarge the magnetization difference Δ M in the inverse martensitic transition for Ni–Co–Mn–In alloys, which is mainly attributed to the variations of the short-range atomic arrangement and electronic structure. As a result, the Δ S M can reach up to 62.17 J/(kgK) only with a small magnetic field of 3 T. Even compared with the Δ S M of other works measured under 5 T magnetic field, this value is much superior and can be further improved up to 136.16 J/(kgK) with increasing the magnetic field to 7 T. Such high Δ S M could improve the attractiveness of the material for the actual application. Graphical abstract: Image 1 Highlights: Dense lattice distortion is induced in Ni45 Mn37 In13 Co5 alloys. The magnetization of ferromagnetic phase is significantly increased. High Δ S M of 136.16 J/(kgK) is obtained under 7 T magnetic field.